2018
DOI: 10.1002/app.47307
|View full text |Cite
|
Sign up to set email alerts
|

Polydimethylsiloxane–PbZr0.52Ti0.48O3 nanocomposites with high permittivity: Effect of poling and temperature on dielectric properties

Abstract: Polydimethylsiloxane (PDMS)/lead zirconate titanate (PbZr0.52Ti0.48O3, PZT)‐based nanocomposites with high dielectric constant (permittivity, k) are prepared through room temperature mixing. The effect of PZT loading on electrical and mechanical properties of the PDMS–PZT composites is extensively studied. It is found that there is significant increase in permittivity with PZT loading and decrease in volume resistivity. All the composites have low dielectric loss compared to permittivity value. It is observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…The presence of these MWCNT‐containing regions may contribute to the increase in local electric field on the PZT particles due to the formation of microcapacitors (in the MWCNT‐PZT‐MWCNT configuration), that is, they can improve the polarization of PZT particles and, in turn, contribute to the piezoelectric properties of the composites. A similar behavior, that is, a two‐phase composite, has also been observed by Nayak for polydimethylsiloxane (PDMS) and PZT 37 …”
Section: Resultssupporting
confidence: 76%
“…The presence of these MWCNT‐containing regions may contribute to the increase in local electric field on the PZT particles due to the formation of microcapacitors (in the MWCNT‐PZT‐MWCNT configuration), that is, they can improve the polarization of PZT particles and, in turn, contribute to the piezoelectric properties of the composites. A similar behavior, that is, a two‐phase composite, has also been observed by Nayak for polydimethylsiloxane (PDMS) and PZT 37 …”
Section: Resultssupporting
confidence: 76%
“…A marginal change in the dielectric constant of all composite films was also observed at frequencies of 1 and 100 kHz. The small increase in the dielectric constant at a low frequency was due to the interfacial and space charge polarization . All the composite films showed relatively lower dissipation factor values.…”
Section: Resultsmentioning
confidence: 94%
“…The small increase in the dielectric constant at a low frequency was due to the interfacial and space charge polarization. 63 All the composite films showed relatively lower dissipation factor values. The dielectric constants and dissipation factors with various contents of MASnBr 3 at 1 and 100 kHz are summarized in Figure 2c.…”
Section: ■ Experimental Sectionmentioning
confidence: 93%
“…reported that barium titanate particles could be used to improve the dielectric behavior of PDMS-based composites . Furthermore, diverse works of nanocomposites with other ceramic fillers consisting of TiO 2 , boron nitride (BN), and PbZr 0.52 Ti 0.48 O 3 have been done to enhance their dielectric constants. Unfortunately, a high volume fraction of ceramic fillers (usually more than 40 vol %) is of great necessity to acquire high permittivity, leading to sacrificing the flexibility and processability of DE composites. When the size of the filler particles decreases, the number of particles per unit volume and the interfacial area will increase, and the interparticle distance will be shorter at a certain loading in the composite.…”
Section: Introductionmentioning
confidence: 99%